Evaluation of Biochemical Parameters in Type 2 Diabetes Mellitus Patients with Non-Alcoholic Fatty Liver Disease at a Tertiary Care Hospital in Bhopal - Darotiya, Seema; yadav, Gayatri (Journal of Neonatal Surgery, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) is a leading cause of chronic liver disease worldwide and can progress to fibrosis and cirrhosis. NAFLD is increasingly prevalent, particularly in individuals with central obesity, type 2 diabetes mellitus (T2DM), dyslipidemia, and metabolic syndrome. Objective: To assess biochemical parameters in patients with T2DM and NAFLD at a tertiary care hospital in Bhopal. Methods: This study was conducted in the Department of Biochemistry at L.N. Medical College and J.K. Hospital, involving 70 subjects diagnosed with T2DM and NAFLD. NAFLD severity was classified into three grades (1–3) based on abdominal ultrasonography findings. Biochemical parameters analyzed included HbA1c, serum cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). Results: Among 70 participants, those with NAFLD Grade 3 had the highest total cholesterol levels (Mean TC = 266 mg/dL). Grade 3 participants (n=17) exhibited elevated triglyceride levels (Mean TG = 246 mg/dL), while Grade 2 participants (n=25) had increased LDL levels. Grade 1 participants had the lowest HDL levels (Mean HDL = 35 mg/dL). Dyslipidemia, characterized by elevated triglycerides or LDL with reduced HDL, was the most common abnormality. Total cholesterol, LDL, and HDL levels were significantly associated with NAFLD severity, whereas triglyceride variations across NAFLD grades were not statistically significant. Conclusion: This study highlights the importance of recognizing fatty liver as a component of metabolic syndrome in individuals with diabetes mellitus. Regular monitoring of lipid profiles in T2DM patients with NAFLD is essential for early intervention and management.